2010
DOI: 10.1002/btpr.477
|View full text |Cite
|
Sign up to set email alerts
|

Downstream antibody purification using aqueous two‐phase extraction

Abstract: The extraction of antibodies using a polyethylene glycol (PEG)-citrate aqueous two-phase system (ATPS) was investigated. Studies using purified monoclonal antibody (mAb) identified operating ranges for successful phase formation and factors that significantly affected antibody partitioning. The separation of antibody and host cell protein (HCP) from clarified cell culture media was examined using statistical design of experiments (DOE). The partitioning of antibody was nearly complete over the entire range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…That means, the output responses are situated in the vicinity of the optimal experimental region, thus the significant factors can be optimized by RSM in the next DoE step [7,14]. On the other hand, when the output responses are far away from the optimal experimental region no difference or curvature is existing, and therefore steepest ascent [16,18,23,24] or steepest descent [25] experiments have to be carried out in order to increase or decrease the output responses, respectively, thus reaching the proximity of the optimal experimental region and investigate the experimental direction [7,9]. These steeptest ascent/descent experiments are initially performed at the center-point of the significant factors and each factor level is increased or decreased according to the magnitude of the main effects [7].…”
Section: Steepest Ascent / Descent Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…That means, the output responses are situated in the vicinity of the optimal experimental region, thus the significant factors can be optimized by RSM in the next DoE step [7,14]. On the other hand, when the output responses are far away from the optimal experimental region no difference or curvature is existing, and therefore steepest ascent [16,18,23,24] or steepest descent [25] experiments have to be carried out in order to increase or decrease the output responses, respectively, thus reaching the proximity of the optimal experimental region and investigate the experimental direction [7,9]. These steeptest ascent/descent experiments are initially performed at the center-point of the significant factors and each factor level is increased or decreased according to the magnitude of the main effects [7].…”
Section: Steepest Ascent / Descent Methodsmentioning
confidence: 99%
“…However, when the experimental region of interest is cuboidal rather than rotatable/ spherical or when it is preferable to maintain low and high factor levels, and still carry out a RSM design, the CCF or face-centered cube is a feasible alternative involving α = ± 1 [9,13], which is commonly used for the optimization of PEG-salt ATPS [2,16,17,22,25,28,31,34,36,[49][50][51][52][53][54][55][56][57]. For instance, in the CCF design for three factors (e.g., x 1 , x 2 , and x 3 ) the star/axial points are located on the centers of the faces of a cube or hypercube (Fig.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…100 The two phases have different hydrophobic properties and hence, cellular debris, particulate matter, and contaminants such as BSA and HCPs tend to move to the lower, more polar phase, while the protein of interest moves to the upper, less polar layer, which is more hydrophobic. 99,100 A successful example of antibody purification by ATPS was achieved by Mao et al 101 using an aqueous-citrate two-phase system. A design of experiment (DOE) screening strategy was used to identify the percentages of PEG, citrate, and NaCl required to achieve optimal separation.…”
Section: Aqueous Two-phase Partitioningmentioning
confidence: 99%
“…The authors found that although the ATPS technique alone produced a modest clearance of HCP, in combination with Protein-A chromatography and size-exclusion chromatography, a purity of 99.5% was achieved. 101 In addition, Platis and Labrou 102 applied the same technique for the isolation of anti-human immunodeficiency virus (HIV) mAbs 2G12 and 4E10 from a transgenic tobacco crude extract. In a similar fashion to the previous ATPS example, Platis and Labrou 102 observed phase partitioning of plant debris/mAb using 13.1 (w/w) PEG 1,500 (kDa), 12.5% (w/w) phosphate at pH 5.…”
Section: Aqueous Two-phase Partitioningmentioning
confidence: 99%
See 1 more Smart Citation